Cassava growth and productive performance at different planting times in the Agreste of Alagoas, Northeastern Brazil - Silva, Ricardo B.; Santos Neto, Antônio L. dos; Santos, Wellington M. dos; Teodoro, Iêdo; Barros, Allan C.; Santos, Valdevan R. dos; Souza, Ademária A. de; Martins, Gleica M. C.; Costa, Bruno R. dos S.; Souza, José W. G. de; Silva, Dayane M. R. (Revista brasileira de engenharia agrícola e ambiental, 2025)
ABSTRACT The aim of this study was to evaluate the influence of different planting times and meteorological variables on the productive performance of industrial cassava in the Agreste region of Alagoas state, Brazil. The treatments were five planting dates, 25 days apart: D1 - April 10, D2 - May 5, D3 - May 30, D4 - June 24 and D5 - July 19. The experiment was conducted from April 2021 to September 2023 (two cultivation cycles), using randomized blocks, with four replicates. The variables analyzed were agrometeorological data, crop growth and yield. In the Agreste region of Alagoas, the average daily ET0 varies from 2.9 to 4.7 mm between the rainy and dry seasons, respectively. The average temperature of 24.3 °C meets the thermal demands of cassava cultivation. Although annual rainfall is sufficient to guarantee cassava production, it is seasonal, with a dry period from spring to summer, which compromises subsequent plantings. In the Agreste region of Alagoas, the best time to plant cassava is from April 10 to May 5, which is the beginning of the rainy season and ensures better vegetative canopy height (3.2 m), stem diameter (2.8 cm), leaf area index (3.0), maximum root length (43.1 cm), number (6.6) and yield (72.8 t ha-1), total biomass (145 t ha-1) and starch content (34.3%). RESUMO O objetivo desta pesquisa foi avaliar a influência de diferentes épocas de plantio e variáveis meteorológicas no desempenho produtivo da mandioca industrial na região do Agreste de Alagoas. Os tratamentos foram cinco datas de plantio, com espaçamento temporal de 25 dias entre elas: D1 - 10 de abril, D2 - 05 de maio, D3 - 30 de maio, D4 - 24 de junho e D5 - 19 de julho. O período experimental foi de abril de 2021 a setembro de 2023, dois ciclos de cultivo. Utilizou-se o delineamento em blocos casualizados, com quatro repetições. As variáveis analisadas foram: dados agrometeorológicas e de crescimento e produção da cultura. Na região do Agreste de Alagoas, entre as estações chuvosa e seca, a ET0 média diária varia de 2,9 a 4,7 mm, respectivamente. A temperatura média do ar é 24,3 °C e atende as demandas térmicas da cultura da mandioca. A precipitação anual é suficiente para garantir a produção de mandioca, porém, há sazonalidade nas chuvas, com período seco da primavera ao verão, o que prejudica plantios mais tardios. Na região do Agreste de Alagoas, o melhor período para o plantio da mandioca é de 10 de abril a 5 de maio, que é o início do período chuvoso da região e garante melhores resultados em: altura do dossel vegetativo (3,2 m), diâmetro do caule (2,8 cm), índice de área foliar (3,0), comprimento máximo (43,1 cm), número (6,6) e rendimento de raízes (72,8 t ha-1), biomassa total (145 t ha-1) e teor de amido (34,3%).